(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article presents the current state of the para-athlete sport, current problems in the development of this sport, types of training, the main tasks of pre-competition preparation of athletes and the content of training for their preparation. Also, the process of training athletes (athletes of class F37 in para-athlete) and the content and standards of the means used in it are presented, and finally, an analysis of the results obtained on their physical fitness is given. At the end of the work, a general conclusion is given.